The State, Religion, and Violence in Colonial and Postcolonial Malawi - Chiudza Banda, Paul (Religions, 2024)
In the histories of both colonial and postcolonial Malawi, there have been cases of religious-related violence, both in its physical and non-physical forms. Such cases have led to the deaths of the “perpetrators” of violence and ‘innocent’ believers, destruction of property, prison detentions, and even the forced removal of citizens from the country. This paper analyzes two case studies, one in which private citizens perpetrated the violence, led by a preacher called John Chilembwe, of the Providence Industrial Mission (PIM), challenging British colonial authorities during the second decade of the twentieth century. In the second case, the focus is on the independent Malawi government, which used violence against members of the Jehovah’s Witness (JW) religious sect from the early 1960s to the early 1990s, owing to the Witnesses’ disassociation from the demands of the secular state. Using data primarily drawn from various archives and other published studies, this paper argues that the use of ‘religious-based violence’ is not just a domain ‘reserved’ for those experiencing oppression, exclusion, and marginalization. Rather, authoritarian governments, like the one that emerged in postcolonial Malawi and other parts of Africa, also resorted to using ‘religious-based violence’ to serve as a tool for eliminating ‘non-conforming’ religious sects and organizations. In doing so, this paper contributes to the various fields of scholarship, including the relationship between religion and violence in modern Africa and the dynamics and operations of the state in both colonial and postcolonial Africa.